Functional disability and its predictors in systemic sclerosis: a study from the DeSScipher project within the EUSTAR group. (11th May 2017) - Jaeger, Veronika K; Distler, Oliver; Maurer, Britta; Czirják, Laszlo; Lóránd, Veronika; Valentini, Gabriele; Vettori, Serena; Del Galdo, Francesco; Abignano, Giuseppina; Denton, Christopher; Nihtyanova, Svetlana; Allanore, Yannick; et al.
Abstract: Objectives: The multisystem manifestations of SSc can greatly impact patients' quality of life. The aim of this study was to identify factors associated with disability in SSc. Methods: SSc patients from the prospective DeSScipher cohort who had completed the scleroderma health assessment questionnaire (SHAQ), a disability score that combines the health assessment questionnaire and five visual analogue scales, were included in this analysis. The effect of factors possibly associated with disability was analysed with multiple linear regressions. Results: The mean SHAQ and HAQ scores of the 944 patients included were 0.87 (s .d . = 0.66) and 0.92 (s .d . = 0.78); 59% of the patients were in the mild to moderate difficulty SHAQ category (0 ⩽ SHAQ < 1), 34% in the moderate to severe disability category (1 ⩽ SHAQ < 2) and 7% in the severe to very severe disability category (2 ⩽ SHAQ ⩽ 3). The means of the visual analogue scales scores were in order of magnitude: overall disease severity (37 mm), RP (31 mm), pulmonary symptoms (24 mm), gastrointestinal symptoms (20 mm) and digital ulcers (19 mm). In multiple regression, the main factors associated with high SHAQ scores were the presence of dyspnoea [modified New York Heart Association (NYHA) class IV (regression coefficient B = 0.62), modified NYHA class III (B = 0.53) and modified NYHA class II (B = 0.21; all vs modified NYHA class I)], FM (B = 0.37), muscle weakness (B = 0.27), digital ulcers (B = 0.20) and gastrointestinal symptoms (oesophageal symptoms, B = 0.16; stomach symptoms, B = 0.15; intestinal symptoms, B = 0.15). Conclusion: SSc patients perceive dyspnoea, pain, digital ulcers, muscle weakness and gastrointestinal symptoms as the main factors driving their level of disability, unlike physicians who emphasize objective measures of disability.